Research achievements of the Qinghai-Tibet Plateau based on 60 years of aeromagnetic surveys - Sheng-qing Xiong (China Geology, 2021)
ABSTRACT: The Qinghai-Tibet Plateau (also referred to as the Plateau) has long received much attention from the community of geoscience due to its unique geographical location and rich mineral resources. This paper reviews the aeromagnetic surveys in the Plateau in the past 60 years and summarizes relevant research achievements, which mainly include the followings. (1) The boundaries between the Plateau and its surrounding regions have been clarified. In detail, its western boundary is restricted by West Kunlun-Altyn Tagh arc-shaped magnetic anomaly zone forming due to the arc-shaped connection of the Altyn Tagh and Kangxiwa faults and its eastern boundary consists of the boundaries among different magnetic fields along the Longnan (Wudu)-Kangding Fault. Meanwhile, the fault on the northern margin of the Northern Qilian Mountains serves as its northern boundary. (2) The Plateau is mainly composed of four orogens that were stitched together, namely East Kunlun-Qilian, Hoh-Xil-Songpan, Chamdo-Southwestern Sanjiang (Nujiang, Lancang, and Jinsha rivers in southeastern China), and Gangdese-Himalaya orogens. (3) The basement of the Plateau is dominated by weakly magnetic Proterozoic metamorphic rocks and lacks strongly magnetic Archean crystalline basement of stable continents such as the Tarim and Sichuan blocks. Therefore, it exhibits the characteristics of unstable orogenic basement. (4) The Yarlung-Zangbo suture zone forming due to continent-continent collisions since the Cenozoic shows double aeromagnetic anomaly zones. Therefore, it can be inferred that the Yarlung-Zangbo suture zone formed from the Indian Plate subducting towards and colliding with the Eurasian Plate twice. (5) A huge negative aeromagnetic anomaly in nearly SN trending has been discovered in the middle part of the Plateau, indicating a giant deep thermal-tectonic zone. (6) A dual-layer magnetic structure has been revealed in the Plateau. It consists of shallow magnetic anomaly zones in nearly EW and NW trending and deep magnetic anomaly zones in nearly SN trending. They overlap vertically and cross horizontally, showing the flyover-type geological structure of the Plateau. (7) A group of NW-trending faults occur in eastern Tibet, which is intersected rather than connected by the nearly EW trending that develop in middle-west Tibet. (8) As for the central uplift zone that occurs through the Qiangtang Basin, its metamorphic basement tends to gradually descend from west to east, showing the form of steps. The Qiangtang Basin is divided into the northern and southern part by the central uplift zone in it. The basement in the Qiangtang Basin is deep in the north and west and shallow in the south and west. The basement in the northern Qiangtang Basin is deep and relatively stable and thus is more favorable for the generation and preservation of oil and gas. Up to now, 19 favorable tectonic regions of oil and gas have been determined in the Qiangtang Basin. (9) A total of 21 prospecting areas of mineral resources have been delineated and thousands of ore-bearing (or mineralization) anomalies have been discovered. Additionally, the formation and uplift mechanism of the Plateau are briefly discussed in this paper.©2021 China Geology Editorial Office.